Lubuszanie dziewiętnastowieczni - Belzyt, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The 19th century saw numerous socio-economic changes in the present-day Lubusz Voivodeship. The most noticeable phenomena were the rapid industrial development of larger cities and dozens of villages, as well as population growth. It should be emphasized that many towns and villages developed at a moderate pace, with populations declining. Therefore, this development was selective across the entire voivodeship. The economic foundations were formed by agriculture and forestry, the textile industry, and - to a lesser extent - the food, timber, mining, metallurgical, and machine industries.
Keywords: przemiany gospodarcze; przemiany ludnościowe; województwo lubuskie; 19 w.; population changes; economic changes; Lubusz Voivodeship; 19th century